Long-Term Nonclinical Pulmonary Safety Assessment of Afrezza, a Novel Insulin Inhalation Powder. (February 2021) - Greene, Stephanie F.; Nikula, Kristen J.; Poulin, Dominic; McInally, Kevin; Reynolds, Jack A.
Afrezza delivers inhaled insulin using the Gen2 inhaler for the treatment of patients with type 1 and type 2 Diabetes. Afrezza was evaluated in long-term nonclinical pulmonary safety studies in 2 toxicology species. Chronic inhalation toxicology studies in rat (26 weeks) and dog (39 weeks) and an inhalation carcinogenicity study in rats were conducted with Technosphere insulin (Afrezza) and with Technosphere alone as a vehicle control. Respiratory tract tissues were evaluated by histopathology and cells expressing proliferating cell nuclear antigen (PCNA) were quantified in lungs of rats. Microscopic findings in rats exposed to Afrezza were attributed to the Technosphere particle component, were confined to nasal epithelia, and consisted of eosinophilic globules and nasal epithelial degeneration. There were no Afrezza-related changes in pulmonary PCNA labeling indices in alveoli, large bronchioles, or terminal bronchioles. Microscopic findings in rats exposed to Technosphere particles included eosinophilic globules, mucus cell hyperplasia, and epithelial degeneration in the nasal cavities. PCNA labeling indices were increased in large bronchioles and terminal bronchioles but not in alveoli. There were no Technosphere particle-related findings in the dog study. Afrezza did not exhibit carcinogenic potential in the 2-year study in rats. These nonclinical inhalation studies support the use of Afrezza in humans over extended periods.